DosR’s multifaceted role on Mycobacterium bovis BCG revealed through multi-omics - Cui, Yingying; Dang, Guanghui; Wang, Hui; Tang, Yiyi; Lv, Mingyue; Liu, Siguo; Song, Ningning (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacterium tuberculosis (Mtb) is an intracellular bacterium that causes a highly contagious and potentially lethal tuberculosis (TB) in humans. It can maintain a dormant TB infection within the host. DosR (dormancy survival regulator) (Rv3133c), has been recognized as one of the key transcriptional proteins regulating bacterial dormancy and participating in various metabolic processes. In this study, we extensively investigate the still not well-comprehended role and mechanism of DosR in Mycobacterium bovis (M. bovis) BCG through a combined omics analysis. Our study finds that deleting DosR significantly affects the transcriptional levels of 104 genes and 179 proteins. Targeted metabolomics data for amino acids indicate that DosR knockout significantly upregulates L-Aspartic acid and serine synthesis, while downregulating seven other amino acids, including L-histidine and lysine. This suggests that DosR regulates amino acid synthesis and metabolism. Taken together, these findings provide molecular and metabolic bases for DosR effects, suggesting that DosR may be a novel regulatory target.